2015
DOI: 10.1371/journal.pgen.1005601
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Selection against Complex Mitotic-Origin Aneuploidy during Preimplantation Development

Abstract: Whole-chromosome imbalances affect over half of early human embryos and are the leading cause of pregnancy loss. While these errors frequently arise in oocyte meiosis, many such whole-chromosome abnormalities affecting cleavage-stage embryos are the result of chromosome missegregation occurring during the initial mitotic cell divisions. The first wave of zygotic genome activation at the 4–8 cell stage results in the arrest of a large proportion of embryos, the vast majority of which contain whole-chromosome ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
237
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(261 citation statements)
references
References 85 publications
(109 reference statements)
19
237
3
2
Order By: Relevance
“…Consistent with aneuploidies affecting preimplantation development, recent studies claimed a higher incidence of chaotic chromosome aneuploidies in biopsies taken from 8-cell embryos (day 3) compared with blastocysts (25) derived from putative mitotic events (7). In particular, results from a survey of 385 cleavage-stage embryos found that survival to blastocyst formation correlates with the number of chromosomal abnormalities detected in blastomeres (25).…”
Section: Aneuploidies and Embryo Progression Arrestmentioning
confidence: 73%
See 1 more Smart Citation
“…Consistent with aneuploidies affecting preimplantation development, recent studies claimed a higher incidence of chaotic chromosome aneuploidies in biopsies taken from 8-cell embryos (day 3) compared with blastocysts (25) derived from putative mitotic events (7). In particular, results from a survey of 385 cleavage-stage embryos found that survival to blastocyst formation correlates with the number of chromosomal abnormalities detected in blastomeres (25).…”
Section: Aneuploidies and Embryo Progression Arrestmentioning
confidence: 73%
“…Apart from uniform aneuploidies originating because of meiotic errors in both gametes, postzygotic errors in chromosome segregation can also occur and contribute to human aneuploidies and may be associated with developmental arrest or congenital abnormalities (7). Mitotic errors during the first cleavage divisions result in mosaicism within the preimplantation embryo and potentially in cell lines with different karyotypes.…”
mentioning
confidence: 99%
“…Aneuploidy rates in human embryos increase with maternal age as a result of meiosis I or II errors (Hassold and Hunt, 2001;Nagaoka et al, 2012;Petronczki et al, 2003). In addition, mitotic errors during-post zygotic cleavage divisions may occur producing mosaic blastomeres containing multiple distinct karyotypes within a preimplantation embryo (McCoy et al, 2015). While PBNT is unlikely to correct meiosis I errors, functional cytoplasm from young donors may reduce incidences of aneuploidy resulting from meiosis II or mitotic errors.…”
Section: Discussionmentioning
confidence: 99%
“…Widely held views on early embryo mortality may reflect an entrenched and biased view of the biology. For example, the Macklon “Black Box” review 20 has been cited over 200 times (Web of Knowledge citations on 10 th October 2016) with many articles explicitly referencing its 30% survival/70% failure value 8, 21, 113, 127133 . Macklon’s quantitative summary in his “Pregnancy Loss Iceberg” (30% implantation failure; 30% early pregnancy loss; 10% clinical miscarriage; 30% live births) is a direct, unedited reproduction of estimates published over 10 years previously 19 .…”
Section: Discussionmentioning
confidence: 99%